Do they understand more? Turkish EFL speakers perception of sentence stress in English - Buczek-Zawiła, Anita (LingBaW. Linguistics Beyond and Within, 2016)
As one of the most prominent elements of intonation sentence stress frequently contributes to the meaning expressed by speakers. It most typically signals details of an utterance information structure, but it also performs a contrastive or emphasizing function, thus expressing focus in the spoken discourse. In English and many other languages its location, while exhibiting certain regularities it additionally determined by extra relevant or relative information. As such, either alone or in combination, it may communicate certain additional shades of meaning that, similarly to the contribution of sentence intonation, may escape the attention of EFL speakers. The paper explores the comprehension sensitivity of Turkish speakers of English when it comes to identifying meaning details contributed by sentence stress. It investigates their awareness as detected through perception of variable sentence stress location. The target group are Turkish advanced speakers of English, with various levels of competence, and only sporadic phonetic training in English for part of them. In a perception-based experiment they were asked to identify the details they perceive. Their results were then compared and analysed, also in relation to what their native language (with a distinction into sentential and focal stress) adds in terms of this module of utterance intonation. Finally, their results were correlated with those achieved by Polish advanced speakers of English as investigated in a similar study conducted earlier. The interpretation of the results reveals that Turkish EFL speakers are more sensitive to the highlighting or contrastive function of sentence stress, achieving overall better result here than when they are to judge its contribution to notion such as politeness or impatience. They are also rather competent at detecting the prominent element in an utterance.